Adenovirus infection of the large bowel in HIV positive patients. Issue 8 (August 1992) - Maddox, A; Francis, N; Moss, J; Blanshard, C; Gazzard, B
Abstract : AIMS: To describe the microscopic appearance of adenovirus infection in the large bowel of human immunodeficiency virus (HIV) positive patients with diarrhoea. METHODS: Large bowel biopsy specimens from 10 HIV positive patients, eight of whom were also infected with other gastrointestinal pathogens, with diarrhoea were examined, together with six small bowel biopsy specimens from the same group of patients. Eight of the patients had AIDS. The biopsy specimens were examined by light microscopy performed on haematoxylin and eosin stained and immunoperoxidase preparations, the latter using a commercially available antibody (Serotec MCA 489). Confirmation was obtained with electron microscopy. RESULTS: The morphological appearance of cells infected with adenovirus showed characteristic nuclear and cellular changes, although the inflammatory reaction was non-specific. Immunoperoxidase staining for adenovirus was sensitive and specific, and the presence of viral inclusions consistent with adenovirus was confirmed by electron microscopy. CONCLUSIONS: The light microscopic features of adenovirus infection are distinctive and immunocytochemistry with a commercially available antibody is a sensitive and specific means of confirming the diagnosis. Further studies of the role of adenovirus in causing diarrhoea in these patients are indicated.